Study and Characterization of Flexible Supercapacitor - Garg, Ruby (My University, 2022)
In this era, the increase in the human population has led to an increase in energy demands. To cope with these rising energy requirements, energy storage is a major concern. The common examples of energy storage devices available are batteries and capacitors. However, the problem with batteries is that it delivers energy at a very slow rate and restrict their usage which requires fast delivery of energy such as flashlights, cameras, etc. On the other hand, the capacitor is a device that can provide fast energy delivery but its capacity to store energy is very limited. So, the motivation is to find an alternative that provides energy density greater than capacitors and power density greater than batteries. To have these benefits, the supercapacitor is a device having both qualities. The main component in the supercapacitor device is the electrode material that plays a vital role in the charge storage mechanism of supercapacitors. A large variety of electrode materials such as carbon derivatives, metal oxides, and conducting polymers are used in supercapacitors. However, in activated carbon, the uneven pore size distributions lead to low capacitance results. Moreover, studies are also carried out on carbon nanotubes and graphene. However, there is a serious limitation in graphene that its layers start getting agglomerated very easily. Further, the pseudocapacitive material such as ruthenium oxide (RuO2) and manganese oxide (MnO2) exhibit high cost and poor conductivity. Hence, it opens new avenues for other metal oxides to be used as electrode materials. While doing the investigations, a variety of new members of two-dimensional (2D) materials are discovered such as metal-organic frameworks (MoF), polyoxometalates (POM), MXene, and black phosphorus (BP). From all of these materials, it has been realized that MXene shows the potential application of using it as an electrode material with an excellent device performance as it is possible to systematically control the separation between their layers. Moreover, the synthesis of copper sulfide has also been carried out in this thesis as it is not widely explored in the literature for supercapacitor applications. Further, the study of doping in MXene has also been performed since doping is the best way to tune the surface activity of electrode material. It has already been studied that the method of nitrogen doping is complex which limits its application in free-standing flexible electrodes. From the available options of dopants, vanadium is considered to be the best choice for doping into the titanium carbide MXene because the atomic size of vanadium (205 pm) is similar to titanium (215 pm). Moreover, alkali metal ions have better interaction with the vanadium atom. As vanadium doping in titanium carbide is not explored much in the literature and thus is considered one of the electrode materials to be studied for this thesis. Further, the structural and electrical properties of electrode materials are highly dependent on the synthesis parameters thus, in this thesis the electrode materials are prepared and characterized by varying the process parameters.The various process parameters during the synthesis of MXene are optimized to obtain its layered accordion-like structure since the spacing between different MXene layers plays an important role in enhancing the supercapacitor performance. The accordion-like structure in MXene is confirmed through the SEM and the presence of (110) peak in XRD at a 2-theta value of 60 degrees. It is also observed from the results that the interlayer spacing of MXene can be altered by varying the process parameters. This thesis thus represents that the process parameters play a crucial role if one has to obtain the best MXene layers structurally as well as electrically. Moreover, the synthesis of copper sulfide as an electrode material has been carried at room temperature by reducing copper sulphate pentahydrate using ascorbic acid as a reducing agent in sodium thiosulphate with 2 hours (h) of total reaction time. The results of SEM and XRD have shown that varying the ratio of sodium thiosulphate and copper sulphate strongly affects the morphology of the copper sulfide formed. The hollow rod structure in copper sulfide helps the electrolyte ions to penetrate better into the electrode material. Thus, controlling of process parameters highly affects the electrochemical performance of the supercapacitor. Further, to tune the properties of optimized MXene, vanadium doping has been introduced by varying the ratio of ammonium vanadate and MXene from 0.025:0.1 to 0.1:0.1 with a step size of 0.025 using a simple hydrothermal method. X-ray diffraction and scanning electron microscopy are conducted to observe the changes in structural properties of vanadium doped MXene. The doping has been incorporated into the electrode material as it will increase the conductivity as well as increase the spacing between the layers so that a greater number of electrolyte ions can interact with the electrode material. Afterward, the electrochemical measurements of the supercapacitor device have been performed over the glass, PET, and PP substrate. The results have shown that the MXene and copper sulfide electrode materials deliver the maximum capacitance with the least arc radii on the glass substrate and as compared to PP and PET substrates because the film on the glass substrate can withstand high temperature. Whereas, the capacitive performance of vanadium doped MXene shown over the graphite substrate is greater than on the glass substrate as graphite is highly conducting in nature. Further, the energy-dispersive X-ray spectroscopy (EDS) shows that the uniform distribution of titanium, carbon, oxygen, and vanadium occurred over the entire nanosheet. The results have shown that the capacitance value of 0.025 V-MXene on the flexible conducting substrate is at par with that of the glass substrate. Further, the radius on the EIS plot of vanadium doped MXene is smaller than that of the undoped MXene which indicates that the vanadium doping made the charge transfer easier. Moreover, the capacitance retention of 92.7% and 82.2% is obtained for 0.025 V-MXene on the graphite and glass substrate respectively after 3000 cycles.
Keywords: Supercapacitor; Flexible; Electrode; Characterisation; Energy Storage